Fabrication of nanostructures through self-assembly of non-ionic amphiphiles for biomedical applications. Issue 36 (20th April 2017) - Prasad, Suchita; Achazi, Katharina; Böttcher, Christoph; Haag, Rainer; Sharma, Sunil K.
Abstract : Non-cytotoxic and non-ionic amphiphiles having supramolecular aggregation behavior were synthesized from biocompatible starting materials using a "greener" chemo-enzymatic method. Abstract : Fabrication of self-assembled nanostructures with defined size and morphology represents a formidable challenge and thus, has gained tremendous momentum in research because of their potential applications in various biological systems. Herein, we report on the synthesis of novel non-ionic amphiphiles using 2, 2-di(prop-2-yn-1-yl)propane-1, 3-diol as a core further functionalized with poly(ethylene glycol) monomethyl ether and alkyl chains employing a chemo-enzymatic approach. Surface tension and fluorescence measurements along with dynamic light scattering studies revealed that all of the amphiphilic systems spontaneously self-assemble in aqueous solution, which is further supplemented by cryogenic transmission electron microscopy. The solubilization behavior of these systems as evidenced from UV-Vis and fluorescence spectroscopy and high performance liquid chromatography suggested the effective encapsulation of hydrophobic entities like Nile red, nimodipine, curcumin and dexamethasone. A comparative study with a standard excipient, Cremophor® ELP demonstrated that our nanocarriers exhibited superior/equivalent solubilization behavior for curcumin. Confocal laser scanning microscopy revealed efficient uptake of encapsulated dye in the cytosol of lung cancer cells, thus suggesting, that the reported amphiphilic systems can transport drugs into cells. A study of cytotoxicity showed that the synthesized amphiphilic systems are non-cytotoxic at the concentrations studied. The release profile of encapsulated Nile red incubated with/without a hydrolase enzyme Candida antarctica lipase demonstrated that the dye is stable in the amphiphilic nanostructures in the absence of enzyme for up to 12 days, however, more than 90% release of the dye occurred in 12 days when incubated with lipase. The results advocate the potential of these nanostructures as prospective drug delivery vehicles.